2020
DOI: 10.1186/s12974-020-1708-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal expression profile of NGF and the two-receptor system, TrkA and p75NTR, in experimental autoimmune encephalomyelitis

Abstract: Background: Nerve growth factor (NGF) and its receptors, tropomyosin receptor kinase A (TrkA) and panneurotrophin receptor p75 (p75NTR), are known to play bidirectional roles between the immune and nervous system. There are only few studies with inconclusive results concerning the expression pattern and role of NGF, TrkA, and p75NTR (NGF system) under the neuroinflammatory conditions in multiple sclerosis (MS) and its mouse model, the experimental autoimmune encephalomyelitis (EAE). The aim of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 83 publications
2
19
0
Order By: Relevance
“…NGF and its receptors, TrkA and p75 NTR , are upregulated in experimentally induced encephalomyelitis in mice [271], a finding that supports other studies suggesting cross-talk between the nervous system and the immune system via NGF [272][273][274][275][276]. Post-ischemic inflammatory responses are known to cause secondary neuronal damage in animal stroke models.…”
Section: Neurotrophins and Ischemic Strokesupporting
confidence: 83%
“…NGF and its receptors, TrkA and p75 NTR , are upregulated in experimentally induced encephalomyelitis in mice [271], a finding that supports other studies suggesting cross-talk between the nervous system and the immune system via NGF [272][273][274][275][276]. Post-ischemic inflammatory responses are known to cause secondary neuronal damage in animal stroke models.…”
Section: Neurotrophins and Ischemic Strokesupporting
confidence: 83%
“…Previous studies have demonstrated the upregulation of proBDNF and its receptor p75 NTR in macrophages, monocytes, and microglia in a variety of neurological conditions, including spinal cord injury 21 and Toxoplasma infection 20 . A more recent study showed that the upregulated p75 NTR was mainly expressed in the anti-inflammatory, but not proinflammatory M1 phenotype microglia in the spinal cord during EAE progression 38 . We have recently demonstrated that proBDNF was preferentially expressed in M2-like monocytes in acute aortic dissection patients 23 .…”
Section: Discussionmentioning
confidence: 98%
“…Notably, the increased expression of p75NTR was mainly found in neurons and astrocytes, which is in line with previously reported studies [ 47 , 48 ]. In addition to neurons and astrocytes, p75NTR was also detected on various immune cells, including peripheral mononuclear blood cells and B lymphocytes, mediating a series of neuroinflammatory responses [ 35 , 49 ]. Furthermore, Choi et al reported that IL-1β and TNF-α upregulate p75NTR expression in neurons and astrocytes via the p38MAPK and NF-κB pathway, causing glial cell proliferation and neuronal cell death [ 33 ].…”
Section: Discussionmentioning
confidence: 99%